Synthesis of [1–11C]Butanol via a facile solid phase extraction protocol. (May 2020) - Waterhouse, Nicole N.; Kothari, Paresh J.; Dooley, Marybeth; Hu, Bao; de Leon, Mony J.; Babich, John; Qu, Wenchao
Abstract: A facile synthesis method for the preparation of [1– 11 C]butanol, a regional cerebral blood flow imaging agent, was developed. Using a solid phase extraction method, the highly polar and volatile molecule [1– 11 C]butanol was quickly concentrated, purified, and released as final product; boasting high radiochemical and chemical purities as well as high radiochemical yields. The final drug product was obtained as a sterile, pyrogen-free solution that conforms United States Pharmacopeia (USP) <823> requirements. Highlights: A facile two-step-one-pot method featured with speedy SPE purification for synthesizing [1– 11 C]butanol was developed. [1– 11 C]Butanol was reliably synthesized in high radiochemical yield and the production process took 37 min time in total. The final drug product (FDP) is suitable for human regional cerebral blood flow imaging study.